Exploring biodiversity and ethnobotanical significance of Solanum species in Uzbekistan: unveiling the cultural wealth and ethnopharmacological uses - Gafforov, Yusufjon; Rašeta, Milena; Zafar, Muhammad; Makhkamov, Trobjon; Yarasheva, Manzura; Chen, Jia-Jia; Zhumagul, Moldir; Wang, Mengcen; Ghosh, Soumya; Abbasi, Arshad Mehmood; Yuldashev, Akramjon; Mamarakhimov, Oybek; et al. (Frontiers in Pharmacology, 2024)
Despite its millennial existence and empirical documentation, the ethnological knowledge of herbs is a more recent phenomenon. The knowledge of their historical uses as food, medicine, source of income and small-scale businesses, and the sociological impacts are threatened due to the slow ethnobotanical research drive. Species of the genus Solanum have long been extensively used in folk medicine to treat various illnesses of humans since the dawn of civilization. All data were systematically obtained from papers, monographs, and books written in Uzbek, Russian, and English through various scientific online databases, including Google, Google Scholar, PubMed, Scopus, Semantic Scholar, Science Direct, and Web of Science using specific keywords focused on eight Solanum species. Eight native and non-native Solanum species as S. dulcamara L., S. lycopersicum L., S. melongena L., S. nigrum L., S. rostratum Dunal., S. sisymbriifolium Lam., S. tuberosum L., and S. villosum Mill. have been recorded in Uzbekistan of Central Asia. In this article we presented recently obtained data on the diversity, morphological characteristics, global distribution, habitat, population status, phenology, reproduction, pharmacology and phytochemistry of these Solanum species in Uzbekistan. Furthermore, relying on a combination of literature reviews and analyses from various scientific papers, we focus on food consumption coupled with global ethnobotanical and ethnopharmacological uses in human diseases of the Solanum species growing in Uzbekistan. Since the dawn of civilization, these eight cultivated and non-cultivated species of Solanum have provided sustainable resources of medicinal plants in Uzbekistan to prevent and treat various human diseases. Based on the collected data, it was shown that Solanum species have not been studied ethnobotanically and ethnomedicinally in Uzbekistan and it is necessary to conduct phytochemical and biotechnological research on them in the future. Traditional uses and scientific evaluation of Solanum indicate that S. nigrum, S. sisymbriifolium and S. tuberosum are one of the most widely used species in some parts of the world. Although considerable progress has been made to comprehend the chemical and biological properties of S. nigrum and S. tuberosum species, more research on the pharmacology and toxicology of these species is needed to ensure the safety, efficacy, and quality of their biologically active extracts and isolated bioactive compounds. Additionally, conducting additional research on the structure-activity relationship of certain isolated phytochemicals has the potential to enhance their biological efficacy and advance the scientific utilization of traditional applications of Solanum taxa.